Manual de estudos: jogos educacionais no ensino de inglês - DUTRA, Gabriela Maria Lima Machado (Universidade Federal do Pará, 2023)
Learning a new language brings many benefits to people. By studying a second language, students develop linguistic, cognitive and social skills. However, generally, students do not actively participate in classes. In this sense, a way to encourage students' motivation, involve them in the proposed activities and help them in their learning process, presents the use of educational games in English language classes. However, this theme is not much addressed during the undergraduate course and this can cause a gap in the training of future teachers on the use of this methodological resource. With this, the present work started from the following focus question: How can a study manual complement the training of students of the Degree in Literature - Qualification in English on the use of educational games in teaching English? The work has the general objective: To elaborate a manual, with elements of in its construction, to complement the initial formation of the students of the Degree in Letters – Qualification in English at UEPA, Belém campus, about educational games. With this, the product “Learn, create and play games: educational games for teaching English” was built. The research addresses concepts about communicative language teaching, games in English language teaching and learning and the practice of educational games in the initial training of English teachers. The research methodology has a qualitative approach and the methodological route has three stages: in the first phase, a bibliographical research was carried out in digital educational platforms such as academic google, eduCAPES, Periodicals of CAPES and BDTD; in the second stage, the documental analysis of the Pedagogical Project of the Language Course – English Language took place and, finally, a questionnaire was applied to the 2nd and 3rd year students and, also, to the professors of the mentioned course. The testing and validation of the product took place at the aforementioned university and course, with 2nd and 3rd year students. During this period, it was possible to refine the contents of the created artifact and confirm usability aspects of the games, after presenting the elements and suggestions of types of games contained in the educational product. In view of this, it is believed that the product has potential in complementing the training of students of the Letters - English Language course, since knowing about the use of games in education not only prepares students for the future of education, but also enriches their training as teachers, offering them additional pedagogical tools and stimulating their creativity and innovation.